2013
DOI: 10.1111/dote.12098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of idiopathic achalasia and Chagas' disease esophagopathy at the light of high-resolution manometry

Abstract: The comparison between idiopathic achalasia (IA) and Chagas' disease esophagopathy (CDE) may evaluate if treatment options and their outcomes can be accepted universally. This study aims to compare IA and CDE at the light of high-resolution manometry. We studied 86 patients with achalasia: 45 patients with CDE (54% females, mean age 55 years) and 41 patients with IA (58% females, mean age 49 years). All patients underwent high-resolution manometry. Upper esophageal sphincter parameters were similar (basal pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Alternatively, achalasia is a motility disorder, caused by lack of relaxation of the lower esophageal sphincter (LES). Despite presenting minor differences, both conditions share essentially an identical clinical presentation and response to treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, achalasia is a motility disorder, caused by lack of relaxation of the lower esophageal sphincter (LES). Despite presenting minor differences, both conditions share essentially an identical clinical presentation and response to treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of this study is that we did not perform videofluoroscopic or manometric test in CG. However, previous manometric studies have well described changes in esophageal motility in CD patients 7,8,14 . Also, studies involving videofluoroscopic swallowing examination have shown that pharyngeal transit duration, sometimes named pharyngeal clearance, is longer in this population 9,11 .…”
Section: Discussionmentioning
confidence: 92%
“…Assessment of esophageal function in CD is performed by radiological examination 12,13 and conventional 8 or high-resolution manometry 14 . So far, studies of muscle electrical activity by surface electromyography (EMG) in patients with CD have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…All of them were performed in endemic countries. Two studies performed by Vicentine et al [ 23 , 24 ] in Brazil included patients with CD and dilatation of the esophagus and one study by Silva et al [ 25 ] also performed in Brazil selected patients with symptoms. These three studies cannot be compared with our study because their cohorts were selected among symptomatic patients or patients with achalasia-like esophagus.…”
Section: Discussionmentioning
confidence: 99%